The practices of psychoanalysis - Aguillaume Torres, Rómulo (International forum of psychoanalysis, 2025)
The practices of psychoanalysis depend, firstly, on the subject we delimit and, secondly, on the setting in which it is carried out, which in turn is determined by the theoretical model on which it is based and the conception of cure it advocates. These three aspects are explored by reflecting on the two psychoanalyses - empirical and hermeneutic - that give rise to the different theoretical positions on fixation and suggestion as the fundamental referents studied here.